PENGEMBANGAN INSTRUMEN PENILAIAN KINERJA UNTUK MENGUKUR KOMPETENSI LABORATORIUM MAHASISWA DALAM KEGIATAN PRAKTIKUM FISIOLOGI TUMBUHAN - Septiana Dwi Utami; Ika Nurani Dewi; Ismail Efendi (Bioscientist : Jurnal Ilmiah Biologi, 2020)
This study aims to: 1) determine the appropriateness of practicum performance appraisal instruments; and 2) find out whether there are differences in competency of laboratory skills among students. The instrument development procedure refers to the 4-D model with a research trial design using one shoot case study. Before the performance appraisal instrument was applied to 77 semester IV students Department of Biology Education, FSTT, Mandalika University of Education, a validation test was first conducted by an expert. Data collection techniques using validation, testing, and observation. The instruments used in this study were instrument validation sheets, observation sheets of action laboratory skills and tests of thinking laboratory skills. Data analysis using the one way ANOVA test continued with the LSD test. The results showed that: 1) the feasibility of performance evaluation instruments developed in the valid and reliable categories; and 2) there were significant differences in laboratory skills in the three groups at ɑ = 5% in the sufficient category. The conclusion of this research is the performance assessment instrument developed can be used to train student laboratory skills. The implications of this research are expected to contribute to improving the quality of practicum assessment instruments in learning in the laboratory.